Iridium-catalyzed asymmetric ring-opening reactions of oxabicyclic alkenes with secondary amine nucleophiles - Yang, Dingqiao; Hu, Ping; Long, Yuhua; Wu, Yujuan; Zeng, Heping; Wang, Hui; Zuo, Xiongjun (Beilstein Journal of Organic Chemistry, 2009)
Iridium-catalyzed asymmetric ring-opening reactions of oxabicyclic alkenes with various aliphatic and aromatic secondary amines are reported for the first time. The reaction gave the corresponding trans-1,2-dihydronaphthalenol derivatives in good yields with moderate enantioselectivities in the presence of 2.5 mol % [Ir(COD)Cl]2 and 5 mol % bisphosphine ligand (S)-p-Tol-BINAP. The trans-configuration of 3f was confirmed by X-ray crystallography.
Keywords: chiral bisphosphine ligand; iridium catalyst; oxabicyclic alkenes; ring-opening reaction

Analytical Profiles of Drug Substances and Excipients - Johnson, B. M.; Chang, P. T. L. (1996)
(For reviews.)

(untitled) - Snyder, S. E.; Aviles-Garay, F. A.; Chakraborti, R.; Nichols, D. E.; Watts, V. J.; Mailman, R. B. (J. Med. Chem., 1995)

(untitled) - Kamal, A.; Gayatri, L. (Tetrahedron Lett., 1996)

(untitled) - Kim, K.; Guo, Y.; Sulikowski, G. A. (J. Org. Chem., 1995)

(untitled) - Perrone, R.; Berardi, F.; Colabufo, N. A.; Leopoldo, M.; Tortorella, V.; Fiorentini, F.; Olgiati, V.; Ghiglieri, A.; Govoni, S. (J. Med. Chem., 1995)

(untitled) - Caple, R.; Chen, G. M. S.; Nelson, J. D. (J. Org. Chem., 1971)

(untitled) - Lautens, M. (Synlett, 1993)

(untitled) - Lautens, M.; Colucci, J. T.; Hiebert, S.; Smith, N. D.; Bouchain, G. (Org. Lett., 2002)

(untitled) - Lautens, M.; Fagnou, K.; Hiebert, S. (Acc. Chem. Res., 2003)

(untitled) - Bates, C. G.; Gujadhur, R. K.; Venkataraman, D. (Org. Lett., 2002)

(untitled) - Lautens, M.; Fagnou, K.; Taylor, M. (Org. Lett., 2000)

(untitled) - Lautens, M.; Dockendorff, C.; Fagnou, K.; Malicki, A. (Org. Lett., 2002)

(untitled) - Murakami, M.; Igawa, H. (Chem. Commun., 2002)

(untitled) - Lautens, M.; Hiebert, S.; Renaud, J.-L. (Org. Lett., 2000)

(untitled) - Lautens, M.; Renaud, J.-L.; Hiebert, S. (J. Am. Chem. Soc., 2000)

(untitled) - Lautens, M.; Fagnou, K. (Tetrahedron, 2001)

(untitled) - Leong, P.; Lautens, M. (J. Org. Chem., 2004)

(untitled) - Lautens, M.; Fagnou, K.; Yang, D.-Q. (J. Am. Chem. Soc., 2003)

(untitled) - Webster, R.; Böing, C.; Lautens, M. (J. Am. Chem. Soc., 2009)

(untitled) - López, F.; Harutyunyan, S. R.; Minnaard, A. J.; Feringa, B. L. (J. Am. Chem. Soc., 2004)

(untitled) - López, F.; van Zijl, A. W.; Minnaard, A. J.; Feringa, B. L. (Chem. Commun., 2006)

(untitled) - Tissot-Croset, K.; Polet, D.; Alexakis, A. (Angew. Chem., Int. Ed., 2004)

(untitled) - Falciola, C. A.; Tissot-Croset, K.; Alexakis, A. (Angew. Chem., Int. Ed., 2006)

(untitled) - Arrayás, R. G.; Cabrera, S.; Carretero, J. C. (Org. Lett., 2003)

(untitled) - Bertozzi, F.; Pineschi, M.; Macchia, F.; Arnold, L. A.; Minnaard, A. J.; Feringa, B. L. (Org. Lett., 2002)

(untitled) - Lautens, M.; Dockendorff, C. (Org. Lett., 2003)

(untitled) - Li, M.; Yan, X.-X.; Hong, W.; Zhu, X.-Z.; Cao, B.-X.; Sun, J.; Hou, X.-L. (Org. Lett., 2004)

(untitled) - Zhang, T.-K.; Mo, D.-L.; Dai, L.-X.; Hou, X.-L. (Org. Lett., 2008)

(untitled) - Cabrera, S.; Arrayás, R. G.; Carretero, J. C. (Angew. Chem., 2004)

(untitled) - Chen, C.-L.; Martin, S. F. (Org. Lett., 2004)

(untitled) - Imamoto, T.; Saitoh, Y.; Koide, A.; Ogura, T.; Yoshida, K. (Angew. Chem., 2007)

(untitled) - Nakamura, M.; Matsuo, K.; Inoue, T.; Nakamura, E. (Org. Lett., 2003)

(untitled) - Lautens, M.; Chiu, P.; Ma, S.; Rovis, T. (J. Am. Chem. Soc., 1995)

(untitled) - Lautens, M.; Ma, S. (J. Org. Chem., 1996)

(untitled) - Lautens, M.; Rovis, T. (J. Org. Chem., 1997)

(untitled) - Rayabarapu, D. K.; Cheng, C.-H. (Chem.–Eur. J., 2003)

(untitled) - Yang, D.-Q.; Long, Y.-H.; Wang, H.; Zhang, Z.-M. (Org. Lett., 2008)